Dual-function AAV gene therapy reverses late-stage Canavan disease pathology in mice - Fröhlich, Dominik; Kalotay, Elizabeth; von Jonquieres, Georg; Bongers, Andre; Lee, Brendan; Suchowerska, Alexandra K.; Housley, Gary D.; Klugmann, Matthias (Frontiers in Molecular Neuroscience, 2022)
The leukodystrophy Canavan disease is a fatal white matter disorder caused by loss-of-function mutations of the aspartoacylase-encoding ASPA gene. There are no effective treatments available and experimental gene therapy trials have failed to provide sufficient amelioration from Canavan disease symptoms. Preclinical studies suggest that Canavan disease-like pathology can be addressed by either ASPA gene replacement therapy or by lowering the expression of the N-acetyl-L-aspartate synthesizing enzyme NAT8L. Both approaches individually prevent or even reverse pathological aspects in Canavan disease mice. Here, we combined both strategies and assessed whether intracranial adeno-associated virus-mediated gene delivery to a Canavan disease mouse model at 12 weeks allows for reversal of existing pathology. This was enabled by a single vector dual-function approach. In vitro and in vivo biopotency assessment revealed significant knockdown of neuronal Nat8l paired with robust ectopic aspartoacylase expression. Following nomination of the most efficient cassette designs, we performed proof-of-concept studies in post-symptomatic Aspa-null mice. Late-stage gene therapy resulted in a decrease of brain vacuoles and long-term reversal of all pathological hallmarks, including loss of body weight, locomotor impairments, elevated N-acetyl-L-aspartate levels, astrogliosis, and demyelination. These data suggest feasibility of a dual-function vector combination therapy, directed at replacing aspartoacylase with concomitantly suppressing N-acetyl-L-aspartate production, which holds potential to permanently alleviate Canavan disease symptoms and expands the therapeutic window towards a treatment option for adult subjects.